A comparative study on biopharmaceutical function of curcumin and miR-34a by multistimuli-responsive nanoniosome carrier: In-vitro and in-vivo - Abtahi, Najmeh Alsadat; Naghib, Seyed Morteza; Haghiralsadat, Fateme; Akbari Edgahi, Mohammadmahdi; Askari, Esfandyar (Frontiers in Molecular Biosciences, 2022)
This research conducted a comparative study on nanoscaled niosomal structures consisting of Tween-80, Tween-60, cholesterol, and dioleoyl-3-trimethylammonium propane (DOTAP). Thin-film hydration technique was used for the preparation and entrapment of curcumin and miRNA in niosomal formulations for enhancing the stability and delivery rate of the agents. Herein, the influence of Tween-80, Tween-60, cholesterol, and DOTAP on the entrapment efficiency (EE%) of curcumin and the physicochemical properties of the carrier are fully discussed. The optimum engineered formulation resulted in a positive charge of +11.23 mV, high EE (100%), smooth surface, spherical shape, small diameter (90 nm), and good stability in physiological buffers. Also, an accelerated cellular uptake, as well as drug release in PBS (pH 7.4, 37°C) after 72 h, were observed. The cytotoxic activity of curcumin (Cur)/miR-34a-loaded nanoparticles was determined by the MTT assay. The results displayed an improved cytotoxic activity of Cur-niosome towards cancer cells compared to free-dispersed Cur. The uptake of Cur-loaded niosome by A280s and A280cp-1 cancer cell lines faced 2.5 folds drop in the concentration compared to its free form. Generally, Cur-niosome exhibits a significant accumulation of superior anti-cancer properties. Likewise, the cytotoxicity of miR-34a-niosome against tumor cells was higher in comparison with its free form. The anti-cancer effects of the gene/drug delivery were investigated in the 4T1 xenografted Balb/C mouse tumor model. According to the in vitro and in vivo results, gene delivery from the modified niosome nanoparticles was distinctly greater than Cur delivery. Therefore, it was concluded that encapsulation of genes in the nano-niosomal delivery system is a promising procedure for the treatment of cancer cells.